E-039 North American Solitaire Stent-Retriever Acute Stroke Registry: Post-Marketing Revascularisation and Clinical Outcome Results As Compared to the SWIFT and TREVO-2 Clinical Trials. (14th July 2013) - Zaidat, O; Castonguay, A; Gupta, R; Sun, C; Martin, C; Mueller-Kronast, N; Holloway, W; English, J; Linfante, I; Dabus, G; Malisch, T; Marden, F; et al.
Abstract : Background: The recent results of the SWIFT and TREVO-2 trials demonstrated better recanalisation and efficacy rates with the SOLITAIRE FR and TREVO devices compared to the MERCI retriever; however, limited post-marketing data exists on use of the SOLITAIRE FR device in clinical practice. The North American SOLITAIRE Acute Stroke (NASA) Registry aimed to assess the real-world performance of the SOLITAIRE FR device in comparison to the results from the SWIFT and TREVO-2 clinical trials. Method: The investigator-initiated NASA Registry recruited clinical sites within North America to submit demographic, clinical presentation, site-adjudicated angiographic and clinical outcome data on consecutive patients treated with the SOLITAIRE FR. Symptomatic intracranial haemorrhage (sICH) was defined as any parenchymal haematoma, SAH, or IVH associated with a worsening of the NIHSS score by ≥ 4 within 24 hours. The primary outcome was achieving TIMI ≥ 2 or TICI ≥ 2a revascularisation. Secondary outcomes were mRS at 3 months, mortality, and sICH. The data was housed and analysed by a central coordinating site, the Medical College of Wisconsin. Results: To date, 343 patients underwent treatment for acute ischaemic stroke using the SOLITAIRE FR device in 20 North American centres. Baseline demographics were: Mean age of 67.3 ± 15.2; Median of 70 (IQR55–79) years of age; the group was equally divided between women 49% (167/343), with majority white 74% (250/343). Median baseline NIHSS was 18 (IQR14–23). Mean time from onset to groin (TOG) was 368.3 ± 241 minutes; mean fluoroscopy time of 33 ± 26 minutes; and a mean procedure time of 103 ± 64.6 minutes. Recanalisation Outcome: The primary outcome showed a TIMI ≥ 2 rate of 83.3% (285/343) and a TICI ≥ 2a rate of 87.2% (299/343), compared to the operator reported TIMI ≥ 2 rate of 83% in SWIFT and TICI ≥ 2a rate of 85% in TREVO-2. Clinical Outcome: The 90-day mRS was available in 90.1% (309/243) of NASA patients. A mRS ≤ 2 was demonstrated in 41.4% (109/309), compared to 37% (SWIFT) and 40% (TREVO-2). The rate of sICH was 10% (34/341), compared to 2% (SWIFT) and 4% (TREVO-2). 90-day mortality was 30.4% (94/309) vs 17.2% Conclusion: The NASA Registry demonstrated that the SOLITAIRE FR device performance in clinical practice is comparable to the SWIFT clinical trial results. Disclosures: O. Zaidat: None. A. Castonguay: None. R. Gupta: None. C. Sun: None. C. Martin: None. N. Mueller-Kronast: None. W. Holloway: None. J. English: None. I. Linfante: None. G. Dabus: None. T. Malisch: None. F. Marden: None. H. Bozorgchami: None. A. Xavier: None. A. Rai: None. M. Froehler: None. A. Badruddin: None. T. Nguyen: None. M. Taqi: None. M. Abraham: None. V. Janardhan: None. H. Shaltoni: None. A. Yoo: None. A. Abou-Chebl: None. P. Chen: None.